(untitled) (Marketing Journal, 2025)
In the new digital world, the convergence of the banking sector and modern technologies brings not only numerous advantages but also certain contradictions. While Fintech companies stand out for their speed, innovative services, and flexibility, traditiona l banks ensure stability, legal framework, and reliability. The competition between these two sectors contributes to the improvement of financial services and customer convenience, while also raising issues of regulation, security, and digital trust. From this perspective, this study explores the integration opportunities and 292 conflicts between Fintech and banks, presenting positive solutions for both financial technologies and banking practices.